"You'd be better off to do the keyhole and make a good job of it" a qualitative study of the beliefs and treatment expectations of patients attending secondary care with degenerative meniscal tears. (February 2021) - O'Leary, Helen; Ryan, Liam G; Robinson, Katie; Conroy, Eimear J; McCreesh, Karen
Abstract: Background: Current clinical practice guidelines for degenerative meniscal tears recommend conservative management yet patients are frequently referred to the consultant orthopaedic surgeon despite a lack of evidence for the use of arthroscopy. Objectives: To explore the beliefs about their condition and treatment expectations of patients referred to a secondary care orthopaedic clinic with a degenerative meniscal tear. Design and Methods: Design and MethodsThis qualitative study involved ten patients who participated in semi-structured telephone interviews. Data were subjected to thematic analysis and findings were reported in accordance with the Consolidated Criteria for Reporting Qualitative Studies. Results: Analysis identified five themes. Participants described beliefs, strongly influenced by magnetic resonance imaging (MRI) results, that damaged structures were causing their knee problems ("The meniscus is busted"), and expected their knee problems to inevitably worsen over time ("It's only going to get worse"). Participants were hopeful the orthopaedic consultation would clarify their problem and lead to a subsequent definitive intervention ("Hopefully they will give me answers"). Most participants viewed surgery as "the quick and straightforward solution" necessary to repair faulty cartilage. Exercise was not seen as compatible with the recovery process by most ("Would I make it worse?"). Conclusions: How participants understand their knee problem contributes to surgical expectations and perceptions that it is not amenable to conservative management. Findings suggest a need to educate both patients and primary care clinicians about the safety and efficacy of exercise as first-line therapy for degenerative meniscal tears. The negative role of MRI in promoting surgical expectations needs further consideration. Highlights: Participants described biomedical beliefs strongly influenced by MRI results. Arthroscopy seen as a straightforward and necessary to repair damaged structures. Participants viewed exercise as incompatible with the recovery process. Education about the safety and efficacy of exercise is indicated.